Investigation of the structure and hardness of quenched sintered materials produced from iron-base alloyed powders (Astaloy E) - Ostovan, Farhad; Matori, Khamirul Amin; Mohamed Yusoff, Hamdan; Yunus, Robiah; Mohamed Ariff, Azmah Hanim; Toozandehjani, Meysam; Meschian, Mohammad Reza (Springer, 2016)
The effect of heat treatment on the microstructure, hardness and density of sintered (1129°C, 45 min) specimens of iron-base powder alloys containing 0.8 – 2.5% C, 2% Cu and additives of chromium- and molybdenum-alloyed Astaloy E iron powder is studied.